Pamięć zdarzeń, które „nigdy nie miały miejsca”. Slavery Memorial Martina Puryeara - Aleksandra Piętka (Załącznik Kulturoznawczy)
This paper delves into the structure of Martin Puryear’s Slavery Memorial at Brown University in Providence, Rhode Island, and how it serves as an example of the commemorative practices employed to confront Americans’ collective oblivion with a historical site touched by the trauma of the enslaved peoples. Drawing on the history of higher education in New England, the author analyzes the artistic devices employed by Puryear to convey the truth about Brown’s involvement in the transatlantic slave trade and the rhetoric of perception imposed by the monument on the viewer. The aim of this paper is to demonstrate how the structure of the Slavery Memorial triggers the process of remembering historical facts that are not so much repressed as non-existent in the local community’s collective consciousness.